Developmentally interdependent stretcher‐compressor relationship between the embryonic brain and the surrounding scalp in the preosteogenic head. Issue 7 (21st January 2022) - Tsujikawa, Koichiro; Saito, Kanako; Nagasaka, Arata; Miyata, Takaki
Abstract: Background: How developing brains mechanically interact with the surrounding embryonic scalp layers (ie, epidermal and mesenchymal) in the preosteogenic head remains unknown. Between embryonic day (E) 11 and E13 in mice, before ossification starts in the skull vault, the angle between the pons and the medulla decreases, raising the possibility that when the elastic scalp is directly pushed outward by the growing brain and thus stretched, it recoils inward in response, thereby confining and folding the brain. Results: Stress‐release tests showed that the E11‐13 scalp recoiled and that the in vivo prestretch prerequisite for this recoil was physically dependent on the brain (pressurization at 77‐93 Pa) and on actomyosin and elastin within the scalp. In scalp‐removed heads, brainstem folding was reduced, and the spreading of ink from the lateral ventricle to the spinal cord that occurred in scalp‐intact embryos (with >5 μL injection) was lost, suggesting roles of the embryonic scalp in brain morphogenesis and cerebrospinal fluid homeostasis. Under nonstretched conditions, scalp cell proliferation declined, while the restretching of the shrunken scalp rescued scalp cell proliferation. Conclusions: In the embryonic mouse head before ossification, a stretcher‐compressor relationship elastically develops between the brain and the scalp, underlying their mechanically interdependent development. Key Findings: Brain and scalp are in a stretcher‐compressor relationship in preosteogenic embryonic head. Elastase and myosin blocker weaken scalp's elasticity and contractility. Scalp's confinement supports brain morphogenesis and cerebrospinal fluid homeostasis. Brain expansion supports scalp cells' stretch‐dependent proliferation. Mechanical brain‐scalp confrontation occurs at 77~93 Pa at embryonic day 13.